ANALISIS DETERMINAN FAKTOR-FAKTOR PENDUKUNG BERHASILNYA DESA WISATA - Devy Widya Apriandi; Ade Guntara Fauzi; Nopa Nurdiansyah (STIESA Press, 2024)
This research investigates how Tourism Village products impact business opportunities in tourism areas. This research was carried out descriptive quantitatively, with questionnaires used to collect primary data and secondary data from various sources. This research involved people who visited or visited the Cibeusi Ciater Subang Tourism Village. The results of data analysis show that Tourism Village products received a positive assessment from respondents, with the Informing Tourism Village Products indicator getting the highest score. Apart from that, respondents considered that business opportunities in the Cibeusi Ciater Subang Tourism Village were quite potential, although there were several things that needed to be improved. This research shows how important it is to improve service quality and increase community participation to increase business opportunities in Tourism Villages. Future research must involve more local parties in the development of Tourism Villages so that local communities are better off.